(untitled) (Global Journal of Human-Social Science, 2026)
The pervasive integration of smartphones into student life presents a significant dichotomy, offering tools for learning while simultaneously introducing substantial detrimental effects on academic performance, psychological health, and social well-being. This paper explores the core harmful impacts stemming from excessive and non-academic smartphone use among students. The primary negative effect is academic distraction, where constant notifications, social media, and online entertainment significantly interrupt concentration during study and class time, leading to reduced productivity, lower engagement, and compromised learning outcomes. Furthermore, extensive smartphone use is strongly linked to sleep disruption, as the blue light emission and late-night use interfere with melatonin production and sleep cycles, resulting in daytime fatigue, irritability, and diminished cognitive function. The risk of smartphone addiction is a growing concern, manifesting as compulsive checking, withdrawal symptoms, and neglect of responsibilities, which exacerbates both academic failure and mental health issues. Psychologically, overuse is associated with heightened levels of anxiety, depression, and stress, often fueled by social comparison and cyberbullying on social media platforms. Finally, students exhibit diminished social skills due to a preference for virtual over face-to-face interaction, alongside potential physical health issues like eye strain, poor posture, and sedentary behavior. In conclusion, while smartphones possess educational utility, their misuse constitutes a major impediment to the overall development and academic success of students, necessitating strategies for self-regulation and digital well-being.